The Effect of Improving Growth Mindset on High School Students' Literacy and Numeracy Abilities in The Independent Curriculum - Tuti Sipahutar; Dedy Juliandri Panjaitan (UIN Sunan Gunung Djati Bandung, 2026)
This study was motivated by the importance of developing a growth mindset to support students’ literacy and numeracy skills in the implementation of the Merdeka Curriculum. The objectives were to analyze the influence of growth mindset ownership, describe the condition of high school students’ literacy and numeracy abilities, and examine the relationship between growth mindset and these skills. This quantitative study employed a correlational design and was conducted at SMA Negeri 1 Perbaungan, SMA Negeri 1 Pegajahan, and SMA Negeri 1 Sei Bamban. Data were collected through literacy and numeracy tests and a growth mindset questionnaire. The findings showed that the mean scores of literacy and numeracy skills were 74.26, 72.00, and 69.84, respectively. Overall, students at SMA Negeri 1 Sei Bamban demonstrated lower achievement than those in the other two schools. The results indicate that growth mindset is associated with students’ literacy and numeracy abilities, highlighting the importance of fostering a growth mindset to improve learning quality and outcomes in the Merdeka Curriculum.